PRAGMATIC FEATURES OF ADVERTISEMENTS OF TOURIST DESTINATIONS: PERSUASIVE STRATEGIES AND CONSUMER ATTRACTION ANALYSIS - Yuldosheva Charos Ollayor kizi (Web of Journals Publishing, 2024)
This thesis examines the pragmatic features inherent in tourism destination advertising, focusing on how advertising elements contribute to effective communication and tourist attraction.
Keywords: tourist destinations, pragmatic elements, speech units, persuasive strategies, emotional communication, social platforms, language units.